Consumer Preferences Toward Marine Tourism Area - Silvy Fauziah; Rudy Aryanto (The Winners, 2012)
The marine zone tourism is growing attracting more tourists. Pramuka Island is marine conservation area enriched with marine biodiversity in coral reefs and other natural resources. To develop this potential tourist destination, a customer-based marketing program is required to attract domestic and foreign tourists. The main vision is to understand tourist preferences for marine tourism activities and facilities. A research was conducted on Pramuka Island as a well-known marine tourism zone. The objective was to determine the key tourist preferences for marine tourism destination. Research methods utilized Cochran Q test and Conjoint analysis where the primary data were obtained from tourist respondents. The result showed that there was a tourist preference based on the five attributes considered most important, namely tourism activities, tourist attractions, types of accommodation, food and souvenirs types. This study provided marine tourism destination management with useful guidance for broader implications of the implementation of marketing programs and tourism attraction. Moreover, the results of this study consolidated the learning of a variety of academic and industrial research papers in particular for the measurement of customer preferences towards marine tourism destination.